The Utililization Of Electrocardiograph (ECG) Monitoring System For Patient With Cardiovascular Disease Based On Community: A Literature Review - Rezky Mulyana; Tuti Afriani (Jurnal Keperawatan Muhammadiyah, 2018)
Introduction: Cardiovascular disease is one of diseases which the highest mortality rate in Indonesia, to solve that problem, patients with cardiovascular diseases should be monitored and controlled.Method: The design of this manuscript uses literature review. Data was retrieved from database research journal used in Science Direct, Proquest, SpringerLink and Wiley and internet searches Online in the period of 2012-2017. Analysis result from paper research was there were 13 journals.Results: Electrocardiogram in the community use wireless sensor, mobile and community platform used receiving, analysing, and transmitting data. The system will make easier to monitor the patient's condition for 24 hours and send data from remote and unlimited locations.Conclutions: This monitoring system can help to detect altered electrical cardiac signal, that will automatically send alarms to server accompanied by google maps to show patient’s location. This system makes nurses easy to change diet plans, cure, and the changes. This system is very flexible, easy to use, cheap, and confidentially ensure patient. This system using online system leads to decrease individual social contacts and allow for delay in data transmission process. This study show that the implementation system can develope to reduce mortality due to heart disease.